Physico-Chemical Properties and Oxygen Species Behavior of Bulk and Modified Vanadium Phosphate Catalyst for Partial Oxidation of N-Butane - Tang, Wen Jiunn (2008)
Vanadium phosphate catalyst is well known for the selective oxidation of n-butane to maleic anhydride process. In this study, the behavior of oxygen species in vanadium phosphate catalysts was investigated using temperature programmed analyses. Besides, the effects of Mo and Te dopants addition and mechanochemical treatment also have been studied. A new method to synthesis VOPO4·2H2O using milling technique (mechanosynthesis) also included in the study. The catalysts were synthesized by calcining the precursor, VOHPO4·0.5H2O in a flow of n-butane in air (0.75% n-butane in air) for 16 h at 733 K. Precursor was obtained by reduction of VOPO4·2H2O using iso-butyl alcohol. The physico-chemical properties of the catalysts were characterized by using x-ray diffraction (XRD), BET surface area measurement, redox titration, inductively coupled plasma-atomic emission spectroscopy (ICP-AES), scanning electron microscopy (SEM) and temperature programmed analyses. The catalytic properties of the selected catalysts were carried out by using temperature programmed reaction (TPRn) and on-line microreactor system. A comparison between the fresh and used catalysts in aerobic and anaerobic condition gave the better understanding about the lattice oxygen species which took part in the selective oxidation. It was found that, certain amount of O2- species which associated with V5+ plays an important role in selectivity for maleic anhydride because no O2- species was detected by temperature programmed reduction (H2-TPR) for the used catalyst in anaerobic condition. This result also supported by TPRn profile for the post O2-desorbed catalyst where the catalyst with only O- species gave no significant selectivity compared to catalyst with both oxygen species (O2- and O-). However, deleterious effect was observed for catalysts with high number of V5+ species (catalysts from mechanochemically treated doped precursors). High amount of O2- species was obtained by H2-TPR for these catalysts. However, this oxygen species only promotes total oxidation as only CO2 was observed in n-butane oxidation. Introduction of Mo and Te into the catalyst precursor did not change the phase of the final catalysts. However the doped catalysts consist only platelets particles and no rosette clusters morphology as usually observed for dihydrate route catalyst. Mechanochemical treatment on the doped precursors did not change the VOHPO4·0.5H2O phase of the precursors but increased the number of β-VOPO4 in the catalysts stage. Besides that, the surface area reduced significantly and the morphology also changed from platelets to blocky shape. According to the TPRn results, all the catalysts from the doped precursor gave higher conversion compared to undoped counterpart. However, the catalysts from mechanichemically treated doped precursors have low selectivity because no intermediate products were observed. A new method of VOPO4·2H2O preparation was successfully carried out using mechanosynthesis method. The product synthesized (VOPO4·2H2O) in 2 h at 1400 rpm using agate materials has lower crystallinity compared to the refluxed counterpart. The surface area for the catalyst produced from the mechanosynthesized VOPO4·2H2O was slightly lower than conventional catalyst but increased after the precursor was mechanochemically treated prior calcination step. Meanwhile, the total oxygen removed for the catalysts from mechanosynthesized VOPO4·2H2O was lower compared to conventional catalyst.